Gender Differences in Foreign Language Anxiety at an Ethiopian University: Mizan-Tepi University Third Year English Major Students in Focus - Gerencheal, Berhane (African Journal of Education and Practice, 2016)
Purpose:This study mainly investigated the possible differences of English language anxiety between female and male students. Methodology:The Foreign Language Classroom Anxiety Scale (FLCAS), developed by Horwitz, Horwitz and Cope (1986), consisting of 33 items was administered to the entire population (28 females and 50 males) of English major third year students at Mizan-Tepi University to measure their anxiety level. The students' first semester English final examination result was used to determine the association between English classroom anxiety and English achievement test result in female and male students. Interviews were also made with six students (top three anxious from each gender) to validate the quantitative results. To this end, descriptive statistics, t-test, and Pearson's Moment Correlation Coefficient were used to answer the research questions. Findings:According to the findings of the study, it was found that females had higher anxiety level in their English classes than their counterpart males. Using the t-test, it was also found that students' anxiety were significantly vary by their gender. The Pearson's Moment Correlation Coefficient showed that there was a significant negative relationship between students' foreign language anxiety and their English achievement, though the debilitative effect of English anxiety were more serious in females with compared to males. The findings of this study demonstrated that significant gender differences in foreign language anxiety were found. Contribution to practice and policy recommendations: Teachers should administer a FLCAS for diagnostic purpose if they cannot identify their highly anxious students by simply looking at them. They should also help students adopt an attitude that mistakes are a part of language learning and will be made by everyone. Further, Teachers should also avoid overcorrection; and rather develop techniques and strategies for error correction that decrease negative affect and build students' low self-esteem.